High-Frequency Oscillatory Ventilation Associated With Inhaled Nitric Oxide Compared to Pressure-Controlled Assist/Control Ventilation and Inhaled Nitric Oxide in Children: Randomized, Non-Blinded, Crossover Study - Fioretto, José Roberto [UNESP]; Batista, Khristiani Almeida [UNESP]; Carpi, Mario Ferreira [UNESP]; Bonatto, Rossano César [UNESP]; Moraes, Marcos Aurelio [UNESP]; Queiroz Ricchetti, Sandra Mara [UNESP]; Batistella, Rafaelle Fernandes [UNESP] (Wiley-Blackwell, 2011)
Purpose: To compare the acute oxygenation effects of high-frequency oscillatory ventilation (HFOV) plus inhaled nitric oxide (iNO) with pressure-controlled assist/control ventilation (PCACV) plus iNO in acute hypoxemic respiratory failure (AHRF) children. Methods: Children with AHRF, aged between 1 month and 14 years under PCACV with PEEP >= 10 cmH(2)O were randomly assigned to PCACV (PCVG, n = 14) or HFOV (HFVG, n 14) in a crossover design. Oxygenation indexes and hemodynamic variables were recorded at enrollment (Tind), 1 hr after PCACV start (T0) and then every 4 hr (T4h, etc.). Results: PO(2)/FiO(2) significantly increased after 4 hr compared to enrollment in both groups [(PCVG-Tind: 111.95 +/- 37 < T4h: 143.88 +/- 47.5 mmHg, P < 0.05; HFVG-Tind: 123.76 +/- 33 < T4h: 194.61 +/- 62.42 mmHg, P < 0.05)] without any statistical differences between groups. At T8h, PO(2)/FiO(2) was greater for HFVG compared with PCVG (HFVG: 227.9 +/- 80.7 > PCVG: 171.21 +/- 52.9 mmHg, P < 0.05). FiO(2) could be significantly reduced after 4 hr for HFVG (HFVG-T4h: 0.53 +/- 0.09 < Tind: 0.64 +/- 0.2; P < 0.05) but only after 8 hr for PCVG. Comparing groups at T8h, it was observed that FiO(2) decrease was greater for HFVG (HFVG: 0.47 +/- 0.06 < PCVG: 0.58 +/- 0.1; P < 0.05). Conclusion: Both ventilatory techniques with iNO improve oxygenation. HFOV causes earlier FiO(2) reduction and increased PO(2)/FiO(2) ratio compared to PCACV at 8 hr. However, at the end of the protocol, there was no significant difference and no clinical improvement derived from the application of both ventilatory strategies with iNO. It is not possible to say what would have happened if a different conventional ventilatory mode and a fully protective ventilatory strategy had been used, given the fact that our study is non-blind, and that a limited number of patients were included in each group. Pediatr Pulmonol. 2011; 46:809-816. (C) 2011 Wiley-Liss, Inc.
Keywords: high-frequency oscillatory ventilation; mechanical ventilation; respiratory failure; inhaled nitric oxide; children